EFFECTIVE STRATEGIES FOR TEACHING READING COMPREHENSION IN ELEMENTARY SCHOOLS - Mr. Shabir Ahmad Dar; Rameez Ahmad Bhat (Journal of International Islamic Law, Human Right and Public Policy, 2023)
Reading comprehension is a fundamental skill for academic success and lifelong learning. This abstract examines effective strategies for enhancing reading comprehension in elementary schools. The paper explores methods such as direct instruction, cooperative learning, graphic organizers, questioning techniques, and technology integration. These strategies are crucial for developing students' ability to understand, interpret, and analyze texts, thereby fostering critical thinking and deeper engagement with learning. Future research should continue to refine and innovate these approaches to meet the diverse needs of elementary students.